1994
DOI: 10.1159/000187988
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Density Lipoprotein on Type IV Collagen Production by Cultured Rat Mesangial Cells

Abstract: Hyperlipidemia, especially hypercholesterolemia, may contribute to glomerulosclerosis as it does to atherosclerosis. Low density lipoprotein (LDL) stimulates the production of extracellular matrix by mesangial cells in culture as well as the proliferation of mesangial cells. This study was carried out to examine the effects of LDL on the type IV collagen (CIV) production by cultured rat mesangial cells (CRMC). Subconfluent CRMC monolayers which were grown in RPMI with 20% lipid-free fetal calf serum for 48 h w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Lipoproteins can also induce the release of cytokines, like TGF-β and PDGF [36, 38]and increase the expression of chemoattractants like m-CSF and MCP-1 by mesangium cells [39, 40, 41]. LDL has also been found to promote in vitro mRNA expression of collagen IV and fibronectin, major components of the extracellular matrix [41, 42]. Our studies indicate a synergistic effect of hyperlipidemia to glomerular injury of hyperglycemia, but do not define the specific pathways by which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoproteins can also induce the release of cytokines, like TGF-β and PDGF [36, 38]and increase the expression of chemoattractants like m-CSF and MCP-1 by mesangium cells [39, 40, 41]. LDL has also been found to promote in vitro mRNA expression of collagen IV and fibronectin, major components of the extracellular matrix [41, 42]. Our studies indicate a synergistic effect of hyperlipidemia to glomerular injury of hyperglycemia, but do not define the specific pathways by which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have postulated that hyperlipidaemia is an important factor in the evolution of glomerulosclerosis [41][42][43]. Thus, Kim et al [44] showed that low-density lipoproteins (LDL) do stimulate in a dose-dependent manner the expression of mRNAs for the a 1 IV collagen chain as well as TIMP-2 in cultured rat mesangial cells. No significant effect of LDL on MMP-2 gene expression was found.…”
Section: Discussionmentioning
confidence: 99%
“…22 In vitro studies have demonstrated that oxidized LDL stimulates the synthesis of collagen by vascular SMCs 23,24 and the expression of type IV collagen by mesangial cells. 25 Thus, these data suggest mutual influences between lipid and collagen that may affect lipid transport mechanisms and deposition as well as collagen synthesis.…”
mentioning
confidence: 81%